Meningkatkan Kemampuan Berhitung Permulaan Anak Usia Dini Melalui Media Pohon Angka Di RA Miftahul Falah - Saripah , Ai; Choiriyah, Choiriyah; Azzahri , Childa Kumala (CV. ITTC INDONESIA, 2024)
AI SARIPAH. Improving the Numeracy Skills of Early Childhood Beginners Through Number Tree Media for class A RA Miftahul Falah Cikajang students, Garut Regency (2024). Thesis.Jakarta: Panca Sakti Bekasi College of Teacher Training and Education. 2024. This research aims to improve the ability to count, one of the aspects that must be developed in early childhood, children aged 4-5 years in the A RA Mifthul Falah group, Cikajang District, Garut Regency. To obtain the data, a numeracy learning outcomes instrument was used in the form of data which was analyzed starting from the pre-cycle, cycle one and cycle two to be compared with percentage descriptive techniques. The research method used is classroom action research (PTK) by applying the Kemmis and Mc Taggart model. The subjects in this research were 10 students at RA Miftahul Falah Cikajang Garut. Data collection was carried out by observation, interviews, checklists. Meanwhile, the data analysis technique uses descriptive analysis. The results of the implementation of cycle I and cycle II in simple exfloration activities using number tree media are presented through several research cycles. Based on the results of the observation phase of learning practices in cycles I and II, recorded in the reflection sheet after learning, it shows that there has been an increase in children's numeracy development through providing stimulation in counting activities using number trees as media. The percentage increase in cycle I was 65.2% and further increased in cycle II to 86.8%, so it can be concluded that this research can increase the ability to calculate using number trees in group A at RA Miftahul Falah. The results of this research provide important meaning for the development of educational policies, especially those related to improving the quality of student learning outcomes.